COMPLIANCE OF WASTEWATER TREATMENT PLANTS IN JÄRVA COUNTY WITH THE EU URBAN WASTEWATER TREATMENT DIRECTIVE AND ESTONIAN NATIONAL REQUIREMENTS - Raili Niine; Enn Loigu; Karin Pachel (European Scientific Journal, ESJ, 2013)
The aim of this study was to assess the treatment efficiency conformity of Wastewater Treatment Plants to the Estonian and European Union requirements in the area of Estonian nitrate vulnerable zone as well as evaluate the existing national wastewater monitoring programme and the efficiency of the self-monitoring programme. Monitoring the results and total pollution load of effluent discharged to the receiving water body from 2007 to 2008 are used to assess the treatment level of WWTPs and the need to establish higher treatment requirements. Estonian national standards, due to the fact that Estonian water bodies are small and vulnerable to pollution, are stricter than the Urban Wastewater Treatment Directive (UWWTD) requirements. If the requirements given in UWWTD are not sufficient to achieve a good status for water bodies, it is proven that wastewater discharge adversely affects the receiving water body and this discharge is one of the important pointpollution sources for water bodies, additional stricter wastewater treatment requirements are needed. WWTPs with a more than a 2,000 population equivalent (p.e.) should be regulated vigorously to guarantee their compliance with the requirements, because WWTPs with more than 2,000 p.e. count for 80% of the total pollution load. A pollution load from WWTPs of less than 2,000 p.e. on the receiving water bodies is marginal; however, the extent of the impact of each individual WWTP depends on, among other things, the characteristics of the wastewater, the turbulence of the receiving water body and the area’s sensitivity as well as other pressure sources.